RECURRENT CENTRAL VENOUS RETINAL OCCLUSION, CLINICAL FEATURES AND TREATMENT OUTCOME - Kjaeva, Jana Nivicka; Sekerinov, Natasa Trpevska; Mehmeti, Gazmend; Petrusevska, Andrijana (Journal of Morphological Sciences, 2023)
Occlusion, thrombosis of the central retinal vein is the second most common vascular disease after diabetic retinopathy. Retinal vein occlusion usually affects the older population. Hypertension, stroke, advanced age, sex, hyperlipidemia are all significant risk factors. Anti-vascular endothelial growth factor agents have been shown to be effective in improving vision at this condition. Aim of this paper is to describe a 38-year-old woman with a medical history of hypertension who was complaining on blurred vision in the left eye. After a complete ophthalmological examination, she started with anti-VEGF treatment. After 3 monthly applications of aflibercept according to the T&E protocol, the treatment continued according to the PRN protocol, during which there was an exacerbation of the disease. Keywords:   central retinal vein occlusion, thrombosis, vascular, vascular endothelial growth factor, aflibercept.